The Psychosocial Impact of Undifferentiated Connective Tissue Disease on Patient Health and Well-Being: A Qualitative Study. Issue 2 (March 2022) - Siegel, Caroline H.; Kleinman, Juliette; Barbhaiya, Medha; Sevim, Ecem; Vega, JoAnn; Mancuso, Carol A.; Lockshin, Michael D.; Sammaritano, Lisa R.
Background/Objective: Despite increased awareness of the diagnosis and treatment of undifferentiated connective tissue disease (UCTD), there is little research on related psychosocial factors. This cross-sectional study qualitatively assesses the psychosocial impact of UCTD on patient health and well-being. Methods: We identified 20 adult patients with UCTD enrolled in the UCTD and Overlap Registry at our tertiary care level hospital. A licensed clinical social worker administered a 30-minute semistructured interview by telephone. The standardized questionnaire consisted of 14 open-ended questions on UCTD. A team of physicians, research coordinators, and a social worker used grounded theory to analyze the qualitative data and identify themes. Results: Among 14/20 study participants (100% female; mean age, 53.6 ± 13.2 years [range, 27–74 years]), all had at least an associate's/bachelor's degree; 9 (64%) were White. The mean disease duration was 14.5 ± 13.5 years (range, 0.5–44 years). Nine study participants (64%) were engaged in counseling or mindfulness training. Ten specific psychosocial themes and categories emerged, including the need for professional guidance and peer and family support to increase awareness, reduce isolation, and promote self-efficacy. Conclusions: Emerging themes from semistructured interviews of women with UCTD at a major academic center suggest the need for psychosocial interventions (e.g., patient support groups, educational materials, peer counselors) to help UCTD patients manage and cope with their illness. Future studies evaluating the psychosocial impact of UCTD diagnosis on diverse cohorts are needed.